2020
DOI: 10.3390/app10093167
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into Micro-Hardness and Wear Resistance of 316L/SiC Composite Coating in Laser Cladding

Abstract: In order to improve the performance of the cladding layer, this study used the Taguchi orthogonal design to investigate the influence of laser power, scanning speed, gas flow, and SiC powder ratio on the micro-hardness and wear volume of the cladding layer. The results indicate that the SiC powder ratio was the major factor that had the main impact on the micro-hardness and wear volume of the cladding layer. The contribution of SiC powder ratio on the micro-hardness and wear volume are 92.08% and 79.39%, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Each of these variables was examined at four distinct levels. A four-factor, four-level orthogonal array design was employed to systematically explore these factors and their interactions [23][24][25]. This design approach, detailed in Table 1, allowed for an e cient experimental setup that minimized the number of trials while maximizing the information obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Each of these variables was examined at four distinct levels. A four-factor, four-level orthogonal array design was employed to systematically explore these factors and their interactions [23][24][25]. This design approach, detailed in Table 1, allowed for an e cient experimental setup that minimized the number of trials while maximizing the information obtained.…”
Section: Methodsmentioning
confidence: 99%
“…In order to better process it, we used the orthogonal experimental design [38,39] to experiment with the processing parameters. Wire breakage is prevented by processing conditions with large pulse widths.…”
Section: Macro-micro Composite Structure Processing Methodsmentioning
confidence: 99%
“…The influence of CeO 2 powers was investigated [ 37 ]. [ [38] , [39] , [40] ] experimentally found that micro-hardness and wear resistance of samples influenced by the material used for cladding and recommended the optimization to maximize the microhardness and minimize the wear in the cladded joints [ 41 ]. utilized Taguchi orthogonal experimental design for optimizing the laser cladding processing parameters [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, using white light interferometry, the 3D morphology of each sample's scratch surface was determined. Each sample's wear volume was then measured [ 39 , 41 ]. The computes assisted universal testing machine of model INSTRON E−3000 was utilized to characterizes the samples for compressive strength.…”
Section: Introductionmentioning
confidence: 99%